„A derék asszony dicsérete": Kommentár a Vetus Testamentum nőképéhez - Hack, Márta (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
As part of the Old Testament and ancient Hebrew wisdom literature, the Proverbs of Solomon describes an ideal for women. In the Old Testament, the image of women is not pejorative, even though from the Fall of mankind, a woman is under the authority of a man. The status of girls and married women in a patriarchal family had somewhat changed for the better under the Law of Moses; although divorce and polygamy were legal, monogamous marriage received indirect protection. The Law also protected women and widows in cases of defamation and, in matters of inheritance as well. This study closes with the analysis of the poetic work of Proverbs 31:10-31, describing an outstanding woman, who is a faithful wife, wise teacher of her children, diligent housekeeper and a talented businesswoman. Her noble character serves as an example and shapes the ideals of women through the ages.